Cytotoxic Assay of Semipolar Fraction Of Ethanolic Extract From Sugar Apple (Annona Squamosa L.) Stem Bark on T47D Cells - Cita Hanif Muflihah; Haryoto Haryoto; Peni Indrayudha (Pharmacon: Jurnal Farmasi Indonesia, 2020)
Previous research has shown that some compounds in leaves and seeds of sugar apple have a cytotoxic activity. The aim of this research was to determine the cytotoxicity of semipolar fraction of ethanolic extract from sugar apple stem bark (Annona squamosa L.) on T47D cancer cells. The semipolar fraction of ethanolic extract from sugar apple stem bark was collected by fractionation using Vacuum Liquid Chromatography (VLC) with hexane:ethyl acetic (9:1, 8:2, 7:3, and  6:4)  as  mobile  phase.  Cytotoxicity from the fractions of five different concentration namely; 25, 50, 100, 150, and 250, µg/mL was measured by MTT assay. The potency of the cytotoxicity was defined by the ability of the fraction to inhibit the growth of T47D cells indicated by the value of IC50. Qualitative analysis of contained compounds in the fraction was done by Thin Layer Chromatography (TLC) method using silica gel F 254 as a stationary phase and hexane:ethyl acetic (7:3) as a mobile phase. UV 254 and 366 nm lamp also Dragendorff, citroboric, and FeCl3 spray reagents were used to visualize the spots of the secondary metabolites. The result proved that the semipolar fraction of ethanolic extract from sugar apple stem bark showed potential cytotoxicity on T47D cancer cells with IC50value of 70,77 µg/mL. Qualitative analysis showed that the fraction contained flavonoids and alkaloids which is presumably responsible for its cytotoxic activity.